1999
DOI: 10.1111/j.1749-7345.1999.tb00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Mineral Absorption by Striped Bass Morone saxatilis Fed a Plant Feedstuff Based Diet Supplemented with Phytase

Abstract: Two experiments were conducted to determine the effects of phytase on growth, apparent phosphorus (P), calcium (Ca), iron (Fe), zinc (Zn), magnesium (Mg), and copper (Cu) absorption, and apparent protein digestibility by striped bass Morone saxatills fed a high phytate diet. In experiment one, four diets with graded levels of phytase supplementation, 0, 500, 1,000, and 2,000 phytase units/kg of diet (PUkg), and a diet supplemented with inorganic P (positive control, total P, 0.73%; phytin P, 0.35%) were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
90
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 43 publications
15
90
0
Order By: Relevance
“…Similar finding was reported on Atlantic salmon that increasing of IP6 inclusion resulted in a progressive decrease of digestibility of Mg and Zn (Denstadli et al, 2006). In contrast, Papatryphon et al (1999) found that Ca was more associated with the phytate complex than other minerals in striped bass.…”
Section: Day S Treatmentssupporting
confidence: 85%
“…Similar finding was reported on Atlantic salmon that increasing of IP6 inclusion resulted in a progressive decrease of digestibility of Mg and Zn (Denstadli et al, 2006). In contrast, Papatryphon et al (1999) found that Ca was more associated with the phytate complex than other minerals in striped bass.…”
Section: Day S Treatmentssupporting
confidence: 85%
“…The advantageous effects of phytase in SBM-containing diets were confirmed in this feeding experiment with improved growth performance, feed conversion, feed efficiency, P and protein digestibility and mineral utilization by Japanese flounder. It has been reported that dietary phytase improved growth and overall performance while reducing P excretion in rainbow trout, Oncorhynchus mykiss (Rodehutscord andPfeiffer 1995, Sugiura et al 2001), carp, Cyprinus carpio (Schafer et al 1995) and striped bass, Morone saxatilis (Papatryphon et al 1999). This study demonstrated that the addition of 150 FTU or more in SBMcontaining diets improved the FCR of Japanese flounder compared to a…”
Section: Discussionmentioning
confidence: 50%
“…The results of the present study indicate that phytase in the diets improved P and protein retention. It is also reported that improved P retention was found with phytase (2000 FTU/kg diet) supplemented in soybean meal and canola meal diets in striped bass (Papatryphon 1999) and in Atlantic salmon (Sajjadi et al 2004). In our study, phytase enhanced protein retention, suggesting that phytase reduces formation of phytate-protein complexes in the gut and causes an improvement in utilization.…”
Section: Effects Of Phytase Addition On P Utilization In Japanese Flomentioning
confidence: 91%
See 1 more Smart Citation
“…However, plant protein sources have limitations related to decreased feed intake due to lack of appetability for shrimp, and by the presence of phytate, an antinutritional factor (AF), which limits bioavailability of phosphorus and other minerals (Lee and Meyers, 1996;Mendoza, Aguilera, & Montemayor, 2000). Phytateor inositol hexaphosphate (myo-inositol-1,2,3,4,5,6-hexaphosphate) is classified as a poly-anionic molecule that may chelate strongly with cations such as Ca ++, Mg ++ , Zn ++ , Cu ++ , Fe +++ , and K + , forming insoluble salts (Kumar, Sinha Makkar, Boech, & Becker, 2011) and reducing absorption of these minerals (Papatryphon, Howell, & Soares, 1999). P excretion is another consequence of the low digestibility of plant ingredients high in phytate and other AF for aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%